The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution VIII. Family Andrenidae, subfamily Panurginae - Astafurova, Yulia V.; Proshchalykin, Maxim Yu. (Zootaxa, 2024)
The type specimens for names of bee taxa in the subfamily Panurginae of family Andrenidae deposited in the Zoological Institute, Russian Academy of Sciences (St. Petersburg) are reviewed. Primary types of 39 taxa are illustrated and detailed information is provided (taxa include 19 described by F. Morawitz; nine by V. Popov; seven by T. Romankova and Yu. Astafurova; three by E. Eversmann; one by A. Osytshnjuk). Panurginus nitidulus Morawitz, 1889 sp. resurr. is resurrected from synonymy with P. nigripes Morawitz, 1880. A new synonymy is established for Camptopoeum rufiventre Morawitz, 1880=C. rufiventre flavovaria Popov, 1936, syn. nov. Panurgus clypeatus Eversmann, 1852 was synonymised with Panurginus labiatus (Eversmann, 1852) but is now recognised as a synonym of Panurginus niger Nylander, 1848, syn. nov. Lectotypes are here designated for the following ten nominal taxa: Camptopoeum altaicum Morawitz, 1891, C. rufiventre flavovaria Popov, 1936, C. schewyrewi Morawitz, 1897, Epimethea variegata Morawitz, 1875, Macrocera nasalis Eversmann, 1852, Panurginus nitidulus Morawitz, 1889, P. semiopacus Morawitz, 1894, Panurgus clypeatus Eversmann, 1852, P. siculus Morawitz, 1871, and Poecilomelitta ornata Popov, 1951.